Faktor-faktor yang berhubungan dengan kegemukan pada balita - Putri Salsabila Azzahra; Setiawati Setiawati; Linawati Novikasari (Holistik Jurnal Kesehatan, 2022)
Background: Obesity prevalence increases worldwide 42 million children are overweight, 31 million in developing countries. Directorate General of Health of the Republic of Indonesia that obesity in toddlers in Indonesia is 14%. In Lampung province reached 21.4%. The prevalence of obesity in toddlers in North Lampung reached 10.72%. Purpose: Knowing the factors related to obesity in toddlers Method: Quantitative analytics using cross-sectional study design. The population is all mothers who have toddlers in Kembang Tanjung Village, North Lampung Regency. The number of samples on as many as 64 responded with 32 cases and 32 controls. Results: Variables proven to be related to obesity are genetic factors p-value 0.001(<0.05), and physical activity factors P-value 0.005(<0.05). Unrelated variables are revenue factors p-value 1.000(>0.05).Conclusion: The majority of respondents are high school-educated, housewives, and the majority of the sex of toddlers are male. There is a relationship between genetic factors and physical activity factors with obesity in toddlers, and there is no relationship between economic factors and obesity in toddlers.Keywords: Obesity; Genetics; Physical Activity; Income; Toddlers.Pendahuluan: Prevalensi kegemukan meningkat diseluruh dunia sebanyak 42 juta anak mengalami kegemukan, 31 juta di negara berkembang. Direktorat Jendral Kesehatan Republik Indonesia bahwa kegemukan pada balita di Indonesia 14%, Provinsi Lampung mencapai 21.4% dan di Lampung Utara mencapai 10.72%.Tujuan: Diketahui faktor-faktor yang berhubungan dengan kegemukan pada balita.Metode: Penelitian analitik kuantitatif dengan menggunakan desain studi cross sectional. Populasinya  semua ibu yang memiliki balita di Desa Kembang Tanjung Kabupaten Lampung Utara. Jumlah sampel pada sebanyak 64 responden dengan 32 kasus dan 32 kontrol.Hasil: Variabel yang terbukti berhubungan dengan kegemukan adalah faktor genetik p-value 0.001(<0.05), dan faktor aktivitas fisik p-value 0.005(<0.05). Variabel yang tidak berhubungan adalah faktor pendapatan p-value 1.000 (>0.05).Simpulan: Hasil penelitian menunjukkan mayoritas responden berpendidikan SMA, pekerjaan sebagai IRT dan mayoritas jenis kelamin balita adalah laki-laki. Ada hubungan antara faktor genetik dan faktor aktivitas fisik, dan tidak ada hubungan antara faktor ekonomi dengan kegemukan pada balita di Desa Kembang Tanjung Kabupaten Lampung Utara.